INTEGRATION OF SCHOOL CULTURE AND MANAGEMENT: AN ANALYSIS OF THE INFLUENCE OF ORGANISATIONAL CULTURE ON EDUCATIONAL EFFICIENCY - Muhammad Mahfud; Fitri Nur Hidayat; Amândio de Araújo Sarmento; Al-Amin (Indonesian Journal of Education (INJOE), 2024)
School management is the process of organising and controlling the resources and activities within a school to achieve predetermined educational goals effectively and efficiently. It includes aspects such as school vision and mission, leadership, communication, resource management and professional development. The research method conducted in this study uses the literature research method. The results show that there are several key factors that influence school management performance. These factors include a clear vision and mission, effective and inspiring leadership, good communication, efficient resource management, and commitment to professional development and innovation. When these factors are considered and managed well, schools can achieve their educational goals more effectively and efficiently